EFFECT OF REPAYMENT CAPACITY AND INSTALLMENT TO DISPOSABLE INCOME RATIO COMPONENTS ON RETURN RATES OF PUBLIC BUSINESS FINANCING (STUDIES AT PT. BANK BRI SYARIAH MALANG SOETTA BRANCH OFFICE) - Rabbani, Salsabila; Anggraeni, Puspitasari Wahyu (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
The ratio of the return rates on nonperforming financing of Islamic banking has not generally been improved. There are several financing problems at PT Bank BRI Syariah Malang Soetta Branch Office in its financial statements. The distribution of micro, small, and medium enterprises financing is not always expeditious due to inaccurate analysis. This study aims to identify and analyze the effect of the components of repayment capacity and installment to disposable income ratio on the return rates of public business financing. This research was a quantitative study with an explanative design. A survey method was the approach used to obtain data. There are 203 debtor data with nonperforming financing at PT Bank BRI Syariah Malang Soetta Branch Office used in this study. The analysis technique used was a comparative analysis. By using logistic regression and comparative analysis, the results show that the RPC components affecting the return rates include working capital, business profits, operating costs, household expenses, business turnover, and BRIS installments.